The prevalence and associated factors for primary headache disorders in adolescents in eastern Sudan: a community-based cross-sectional study - Omar, Saeed M.; Osman, Osman M.; Al-Nafeesah, Abdullah; AlEed, Ashwaq; Alfaifi, Jaber; Adam, Ishag (Frontiers in Neurology, 2024)
Background Headache disorder is the second-highest cause of disability worldwide; however, data are scarce on headache among adolescents, especially in Africa. There has yet to be published data on headache among adolescents in Sudan, the third-largest country in Africa. This study aimed to assess the prevalence of primary headache disorders and associated factors among adolescents (10–19 years) in eastern Sudan. Methods A community-based cross-sectional study was conducted in the city of Gadarif in eastern Sudan. Questionnaires were used to gather the adolescents’ sociodemographic characteristics. Headache diagnostic questions were based on the beta version of the International Classification of Headache Disorders-III (ICHD-3). Multivariate analysis was conducted to assess the associated factors for primary headache disorders, and the results were expressed as risk ratios (RRs) and 95.0% confidence interval (CI). Results Of the 401 enrolled adolescents, 186 (46.4%) and 215 (53.6%) were male and female, respectively. The median (IQR) age was 14.0 (12.1–16.2) years. Eighty-one (20.2%) of the 401 adolescents reported experiencing primary headache disorders, including migraine with aura in 16 (4.0%), migraine without aura in 33 (8.2%), tension-type in 14 (3.5%), and undifferentiated headache in 18 (4.5%) adolescents. The prevalence of primary headache disorders was significantly higher in females than in males [55/215 (67.9%) vs. 26/186 (32.1%), p = 0.004]. In the multivariate analysis, increased age (RR = 1.09, 95.0 CI = 1.02–1.16) and being female (RR = 1.75, 95.0 CI = 1.14–2.67) were associated with increased RR of primary headache disorders. Parents’ education level and occupation, smoking/snuff use, and body mass index were not associated with primary headache disorders. Conclusion One-fifth of the adolescents in eastern Sudan reported experiencing primary headache disorders, which was more common in females and with increased age.